Reconstructing Indonesia's Asset Recovery Policy through Non-Conviction Based Asset Forfeiture to Achieve Substantive Justice - Irdanul Achyar; Faisal Santiago (Jurnal Smart Hukum (JSH), 2027)
This study aims to analyze the problematic asset recovery policy within the Indonesian legal system and to reconstruct the implementation of Non-Conviction-Based Asset Forfeiture (NCBAF) as an asset recovery instrument grounded in substantive justice. The study uses a normative juridical method with a statutory and analytical approach. The results indicate that Indonesia's asset recovery mechanism still relies on conviction-based asset forfeiture, which requires a final and binding criminal decision. Therefore, it is ineffective in situations where the perpetrator dies, absconds, or cannot be prosecuted, even though the assets resulting from the crime can still be identified. The implementation of NCBAF has an adequate conceptual and legal basis as long as it is implemented based on the principles of the rule of law, due process of law, proportionality, judicial oversight, and protection of the rights of third parties acting in good faith. Policy reconstruction is carried out through the establishment of comprehensive regulations regarding the scope of assets, confiscation procedures without a criminal conviction, evidentiary mechanisms, protection of constitutional rights, and harmonization with the national legal system to achieve effective asset recovery, provide legal certainty, and reflect substantive justice.